2015
DOI: 10.11648/j.ajbls.20150305.11
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Substance Use and Risky Sexual Behaviour Among Public College Students in Bonga Town, Southwest Ethiopia

Abstract: Background: Substance use and problems arising from it are increasing all over the world, and currently together with HIV/AIDS epidemic, become one of the most threatening and challenging social and public health problems. College students are more vulnerable to wider sexual and reproductive health and HIV/AIDS problems due to new environment with poor protection, age and the need to explore life, peer pressure and absence of proactive programs. Objective: The main objective of this study was to assess the mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 18 publications
2
9
1
Order By: Relevance
“…In this study, students with poor knowledge of STIs were more likely to develop STIs than students with good knowledge. This finding agrees with those of other studies conducted in Mekelle [25], Wolaita Sodo University [27], and Bahir Dar town [33].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, students with poor knowledge of STIs were more likely to develop STIs than students with good knowledge. This finding agrees with those of other studies conducted in Mekelle [25], Wolaita Sodo University [27], and Bahir Dar town [33].…”
Section: Discussionsupporting
confidence: 93%
“…The finding from this study was higher when compared with Ethiopian Demography and Health Survey (EDHS) 2011 report, among the youth (4%) [19], Bonga college students (13.9%) [27], Bahir Dar University students (6.4%) [28] and high school students in Gondar (10.7%) [29]. The possible difference from the EDHS report might be due to that EDHS survey was a population-based survey which included youth who are living with, and are under the control of the family.…”
Section: Discussionmentioning
confidence: 58%
“…However, recent studies indicated very few youth contacts dealt with life skills and service utilization is still lagging to 12% in Addis Ababa, where high service utilization is expected. 7 , 9 – 14 Schools were a good place where adolescents can share their life experiences and abilities both positively and negatively. Hence, understanding the association between the life skills and sexual behavior of adolescents is decisive in designing adolescent-centered sexual and reproductive health and provide an insight on whether to include the life skills in school health activities.…”
Section: Introductionmentioning
confidence: 99%
“…The current prevalence of chewing khat is 259 (45.7%). These findings are higher than the study conducted on Jimma university internship medical student 13.4% (20), Jimma town high school students 14.2% (14), Bonga public college student 11.4% (15), Woreta high school adolescents 13.8%, Bale preparatory school students 5.6% (12), Debre Berhan university student 5.7% (19) and Ethiopian Demographic and Health Survey report (8). The current study finding was higher than previous study conducted in different parts of Ethiopia due to difference study population, design and setting.…”
Section: Discussionmentioning
confidence: 61%
“…The Town has 17 Kebeles with a total population of 205,163 of whom women account for 102,007, male, 103,156, and a total household of 42,742 according to the 2019 Jimma zone health bureau projection population report. Of the total population, around 40,539 (21%) populations are youth (age found [15][16][17][18][19][20][21][22][23][24].…”
Section: Study Design Period and Settingmentioning
confidence: 99%